The assessment of the hydrocarbon potential and maturity of Silurian intervals from eastern part of Moesian Platform – Romanian sector. (November 2016) - Colţoi, O.; Nicolas, G.; Safa, P.
Abstract: The aim of this paper is the assessment of the hydrocarbon potential and maturity of Silurian intervals from the Călăraşi-Bordei Verde-Biruinţa perimeter – East Moesian Platform. All the information gathered from the wells drilled in the mentioned perimeter is used for the evaluation of the "shale gas" potential, too. This major sedimentary basin has all geological conditions for hydrocarbons generation, migration and accumulation. The main conclusions of the all geo-analyses are the following: the XRD analyses show that the samples consist of clay minerals with organic material, the organic matter contained in the samples of the wells shows widely distributed type of organoclasts. In absence of true vitrinite originating from higher plants in these Lower Paleozoic series, the various encountered organic remains consist of Tasmanites, microporous or homogeneous fragments, structured fragments of graptolites, oxidized or naturally rich in oxygen organoclasts inherited from the continent (phytoclasts, fungal remains). The maturity of the Silurian at Ţăndărei borehole is established taking into account the fluorescence of the Tasmanites and the reflectance of graptolites; the maturity increases with depth between 0.70 and 1% eq. VRo. The organic matter of Biruinţa and Călăraşi boreholes is overmature with maturity of around 1.40–1.55% at 400 m in Biruinţa and a maturity increase with depth between 1.85 and 2.05% eq. VRo in Călăraşi borehole. Those values are mainly deduced from vitrinite/graptolite correlation. According to the maturity trend deduced of Călăraşi and Ţăndărei boreholes, the high maturity of Biruinţa for such a low burial (around 400 m) indicates a possible erosion around 3400 m due to uplift. The Silurian studied samples consist of carbonated claystones with an organic matter of type II with relatively low residual TOC content: less than 1.2% weight for the overmature boreholes (Biruinţa and Călăraşi) and less than 1.6% weight in Ţăndărei borehole. Highlights: The organic matter of samples show widely distributed type of organoclasts. The maturity was evaluated by analysis of the Tasmanites fluorescence and reflectance of graptolitic material. The organic matter belongs to type II with residual TOC content and is in overmature stage.